On the Shallow-Water Harmonic Tidal Constituents - Franco, A. dos Santos (The International Hydrographic Review, 2015)
This is an investigation of the physical law governing the interaction of the astronomical tidal constituents which generates the shallow-water tidal constituents, for the simple case of a narrow channel. The solution for both progressive and standing waves, up to the fifth order, is presented. The fluid is supposed non-viscous, and the flow frictionless.